Public Morality in Indonesian Penal Code Draft: Zina Definition Debate - Hary Widyantoro (Justicia Islamica, 2018)
Bahasan tentang dihidupkannya kembali hukum zina di negara-negara mayoritas Muslim dilakukan oleh Kepala Hukum Pidana yang mendapat banyak perhatian dari segi nasional dan internasional. Penelitian ini menguji kontestasi definisi Zina antara aktor. Ia berpendapat bahwa nilai-nilai agama telah menjadi kerangka kerja untuk menjadikan moralitas menjadi urusan publik melalui hukum reformasi, di negara mayoritas Muslim Indonesia yang majemuk. Kontestasi antara tempat-tempat keagamaan dan sekuler dalam proses, sebagai bagian dari islamisasi yang sedang berlangsung. Data dari media yang dikumpulkan, seperti surat kabar online dan program TV One (Indonesian Lawyers Club) di mana para aktor terlibat dalam membangun wacana gender, seksualitas, dan regulasi di Indonesia. Oleh karena itu, ini berkontribusi pada diskusi mengenai masalah gender dan seksual di negara-negara mayoritas islam, di mana ide-ide agama dan sekuler dipertentangkan.A heated debate at the end of 2017 to the beginning of 2018 in Indonesia, on zina redefinition in Indonesian Penal Code that received both national and international attention, as becoming an interesting study discussing the revival of Zina law in Muslim majority countries. This study examines the contestation over Zina definition between actors. It argues that religious values has become framework to make morality becomes public matter through the law reform, in Indonesian plural Muslims majority country. The contestation between religious and secular took place in the process, as part of ongoing Islamization. The data is collected from media, such as online newspaper and the TV One Indonesian Lawyers Club program where actors were involved in constructing the discourse of gender, sexuality, and its regulation in Indonesia. Hence, this contributes to the discussion on gender and sexuality in Muslims majority countries, where religious and secular ideas are contested.